2022
DOI: 10.1111/rec.13645
|View full text |Cite
|
Sign up to set email alerts
|

Trends and knowledge gaps on ecological restoration research in the Brazilian Atlantic Forest

Abstract: Given the current global environmental crisis, restoring degraded ecosystems stands out among the nature-based solutions to mitigate climate change, reestablish ecosystem services, and maintain biodiversity and human well-being. The high biodiversity of the Atlantic Forest (AF) and its severe degradation turned it into a "restoration hotspot." We performed a bibliometric analysis of the research on restoration of the Brazilian AF to identify thematic trends, potential gaps, as well as networks and benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Según destacaron Rosenfield & Müller (2020) y Zupo et al (2022), actualmente, en el escenario de cambio climático y alteraciones en el uso del suelo, los proyectos de restauración deben tener en cuenta, en su planificación y monitoreo, además de la composición florística, las características funcionales de las especies y del ecosistema. Sin embargo, la aproximación de atributos funcionales en la restauración depende de la disponibilidad de información sobre estas características para las especies utilizadas (Carlucci et al, 2020;Petisco-Souza et al, 2020).…”
Section: Resultado Y Discusiónunclassified
“…Según destacaron Rosenfield & Müller (2020) y Zupo et al (2022), actualmente, en el escenario de cambio climático y alteraciones en el uso del suelo, los proyectos de restauración deben tener en cuenta, en su planificación y monitoreo, además de la composición florística, las características funcionales de las especies y del ecosistema. Sin embargo, la aproximación de atributos funcionales en la restauración depende de la disponibilidad de información sobre estas características para las especies utilizadas (Carlucci et al, 2020;Petisco-Souza et al, 2020).…”
Section: Resultado Y Discusiónunclassified
“…Moreover, the study of some ecological processes remains in force in this phase, such as seed dispersal (da Silva et al 2015). In recent years, efforts have included utilizing functional traits to select species that offer specific ES during restoration and understanding species' responses to environmental filters (Carlucci et al 2020; Zupo et al 2022). Evolutionary relationships between co‐occurring species have also been studied to provide insights into trait conservatism and community assembly processes influencing restoration forest trajectory (Schweizer et al 2015).…”
Section: Forest Restoration In the Baf: Evolution Of Methods Concepts...mentioning
confidence: 99%
“…These include pivotal events such as the adoption of the new Forest Code in 2012 (Pinto et al 2014), the increase in programs that involve PES (Ruggiero et al 2019), a substantial rise in direct seeding practices (Meli et al 2018), and more recently, the proliferation of carbon sequestration initiatives (Gardon et al 2020 b ). Studies published in the last decades collectively contribute to a comprehensive understanding of ecological restoration in the BAF by offering insights into assessing restoration effectiveness, identifying advancements and gaps, proposing strategic approaches, and highlighting research trends and gaps (Strassburg et al 2018; Mendes et al 2019; Guerra et al 2020; Oliveira et al 2021; Zupo et al 2022). In light of its comprehensive nature compared to other phases, we have encompassed the period 2004–2022 as a single phase.…”
Section: Forest Restoration In the Baf: Evolution Of Methods Concepts...mentioning
confidence: 99%
“…Numerous studies have confirmed that the implementation of restorative measures is poised to abbreviate the recovery timeline and expedite the achievement of a robust natural reference condition [15][16][17]. Within this context, commencing from the 1980s, practical activities and research on the restoration of degraded riparian ecosystems have emerged globally to contain or mitigate the negative impacts of dams and other anthropogenic activities [13,18]. As a result, riparian restoration has emerged as a realm of profound scientific interest and noble endeavor, resulting in a surge of related publications.…”
Section: Introductionmentioning
confidence: 99%